Live Imaging and Analysis of Vasoactive Properties of Drugs Using an in-ovo Chicken Embryo Model: Replacing and Reducing Animal Testing. (August 2019) - Swaminathan, Akila; Balaguru, Uma Maheswari; Manjunathan, Reji; Bhuvaneswari, Srinivasan; Kasiviswanathan, Dharanibalan; Sirishakalyani, Bandi; Nayak, Prasunpriya; Chatterjee, Suvro
Abstract: Vasodilation occurs as a result of the relaxation of the smooth muscle cells present in the walls of blood vessels. Various suitable models are available for the analysis of the vasoactive properties of drugs with therapeutic applications. But all these models have limitations, such as ethical issues and high cost. The purpose of this study is to develop an alternative model for studying the vasoactive properties of drugs using an in-ovo chicken embryo model. In the preliminary experiment, we used a well-known vasoconstrictor (adrenaline) and a vasodilator (spermine NoNoate) in the chick embryo area vasculosa and evaluated their concentration-response curve. Adrenaline (10 µ M) and spermine NoNoate (10 µ M) were administered in different arteries and veins and different positions of the right vitelline artery of the chick embryo. Results showed the middle of the vessel bed of the right vitelline artery having the best vasoactive effect compared to others. Finally, anti-hypertensive drugs, calcium channel blockers, and NOS agonists were administered in the chick embryo area vasculosa to validate the model. Results demonstrate that the chick embryo area vasculosa can be an alternative, robust, and unique in-ovo model for screening of anti-hypertensive drugs in real time.